KARAKTERISTIK DAN POTENSI RUANG PESISIR SANUR KAUH DAN SIDAKARYA UNTUK PENGEMBANGAN EKOWISATA DI KECAMATAN DENPASAR SELATAN - I Wayan Suadi Putra (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
The research was conducted on the coast of Sanur Kauh Village and Sidakarya Village, South Denpasar, with the background of the potential use of space for ecotourism activities in the area, in the form of mangroves, Taman Inspirasi Beach, Muntig Siokan Beach and fishing communities. This potential has been included in Perda No.3 / 2019 concerning the Regional Tourism Development Master Plan for 2018-2029, for further, on the proposal of the Government of Sanur Kauh and Sidakarya, in the Revised Regional Regulation RTRW and Ranperda RTDR for Denpasar City, the research area is included in zoning tourist areas. The research objective was to determine the characteristics and potential of area space utilization for ecotourism activities seen from the ecotourism opportunity spectrum component, as well as the suitability of the activities with the ecotourism principle, so that the results can be used as a reference for stakeholders related to the discussion of the Ranperda above. This research uses a qualitative approach, which produces descriptive data, as well as a deductive mindset, where theory becomes a research tool from selecting and finding problems as well as observing in the field to testing the data. The results showed that the Taman Inspirasi Beach area approached the eco-generalist spectrum, and the Muntig Siokan Beach Area approached the eco-specialist spectrum. The research area can apply the principles of ecotourism. The Inspiration Park management needs to be accompanied by a body formed by the government as a control, and it is necessary to form a management agency for the Muntig Siokan Area.